2013
DOI: 10.1007/s11356-013-1603-3
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization does not always mean detoxification: case study of a newly isolated Pseudomonas peli for decolorization of textile wastewater

Abstract: The textile industry is a favor to the Tunisian economy by offering several job positions. However, it's not environmentally friendly. In fact, textile industries discharge high volumes of wastewater which contain several toxic pollutants such as dyes, fixator, and whiteness. In our study, Pseudomonas peli, isolated and characterized from Oued Hamdoun (center of Tunisia), was found able to decolorize textile effluent about 81 % after 24 h shaking incubation. On the other hand, the in vitro antiproliferative ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…MEDICEF is one of the pharmaceutical industries (located in the Sidi Thabet citynorth of Tunisia) that produce many antibiotics; however, at the same time, it discharges its effluent directly in the CEF-river causing many environmental problem. For this, these effluents were treated using biological process with P. peli bacterium isolated from ''Oued Hamdoun-River'' which is polluted by some polycyclic aromatic hydrocarbons (PHAs) including dyes, organophosphorous and so on (Dellai et al, 2013). Despite the presence of various concentrations of antibiotics, P. peli exhibited high ability to grow on the studied IPW and showed remarkable specific growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MEDICEF is one of the pharmaceutical industries (located in the Sidi Thabet citynorth of Tunisia) that produce many antibiotics; however, at the same time, it discharges its effluent directly in the CEF-river causing many environmental problem. For this, these effluents were treated using biological process with P. peli bacterium isolated from ''Oued Hamdoun-River'' which is polluted by some polycyclic aromatic hydrocarbons (PHAs) including dyes, organophosphorous and so on (Dellai et al, 2013). Despite the presence of various concentrations of antibiotics, P. peli exhibited high ability to grow on the studied IPW and showed remarkable specific growth.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterium used in this study was isolated from the Oued Hamdoun River (area of pollutant discharge from textile industries). This strain was identified as P. peli, a nonpathogenic and aerobic bacterium (Dellai et al, 2013). P. peli strain was then inoculated many times in Mueller-Hinton solid agar medium supplemented with 5% of PW (filtered at 0.22 mm) in petri dishes in order to acclimatize the strain.…”
Section: Materials and Methods Biodegradationmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, our results show that the efficiency of WW detoxification differs among laccases and is dependent on the chemical composition of WWs. Previous work has demonstrated WW decolorization and detoxification by laccases from Pseudomonas peli (Dellai et al 2013) and Trametes hirsuta (Abadulla et al 2000). Application of a natural laccase-mediator such as acetosyringone is a less effective decolorizing agent but usually generates nontoxic products.…”
Section: Efficiencies Of Ww Decolorization and Detoxification Differ Among Laccases And Depend On Wastewater Propertiesmentioning
confidence: 99%
“…However, laccases are most frequently used for decolorization and on inhibition of the growth of different microorganisms or seed germination (phytotoxicity test) (Benzina et al 2013) can be used to determine toxicity. Both increases in toxicity of WW treated with laccases (Benzina et al 2013;Dellai et al 2013) and detoxification of WW by laccases (Guan et al 2015;Khlifi et al 2010) have been reported. Optimizing the WW decolorization conditions based on the properties of the laccases used and incorporating product toxicity analysis are, therefore, important considerations for effective biotechnological application of these enzymes.…”
Section: Introductionmentioning
confidence: 96%